IMPLEMENTATION OF TEACHING AND LEARNING APPROACHES FOR INFANTS AND CHILDREN ATTENDING TASKA TO MEET THE ASPIRATIONS OF TODAY’S PARENTS - ATHIRAH ABDUL KUDUS; MOHD NAZRI ABDUL RAHMAN (P3I UMSurabaya, 2025)
This study aims to examine the implementation of a teaching and learning approach (PdP) for infants and toddlers at TASKA that is able to meet the aspirations of today's parents. This study was conducted using library research methods through analysis of journals, academic articles and reports related to early childhood education in Malaysia and internationally. The results show that approaches such as game-based learning (play-based learning), multisensory activities, and learning based on daily routines are the most used methods in PdP at TASKA. This approach is proven to support the holistic development of children that covers cognitive, emotional, social, and motor aspects, as well as being in line with the aspirations of parents who demand quality and safe early education. However, its implementation still faces challenges such as a lack of trained teachers, resource constraints, and the perception of parents who are still inclined to traditional academic approaches. This study suggests that the professional training of teachers be improved, facilities and facilities at TASKA be improved, and communication between teachers and parents be strengthened to ensure a more effective PdP. The results of this study are expected to be a guide to policy makers, TASKA managers, and educators in improving the quality of early childhood education in Malaysia.